Advances in progressive supranuclear palsy: new diagnostic criteria, biomarkers, and therapeutic approaches - Boxer, Adam L; Yu, Jin-Tai; Golbe, Lawrence I; Litvan, Irene; Lang, Anthony E; Höglinger, Günter U (Lancet neurology, 2017)
Progressive supranuclear palsy (PSP), previously believed to be a common cause of atypical parkinsonism, is now recognised as a range of motor and behavioural syndromes that are associated with a characteristic 4-repeat tau neuropathology. New research criteria that recognise early presentations of PSP and operationalise diagnosis of the full spectrum of clinical phenotypes have been reported. The Movement Disorders Society PSP diagnostic criteria include syndromes with few or mild symptoms that are suggestive of underlying PSP pathology and could provide an opportunity for earlier therapeutic interventions in the future. These criteria also include definitions for variant PSP syndromes with different patterns of movement, language, or behavioural features than have been conclusively associated with PSP pathology. Data from new diagnostic biomarkers can be combined with the clinical features of disease to increase the specificity of the new criteria for underlying PSP pathology. Because PSP is associated with tau protein abnormalities, there is growing interest in clinical trials of new tau-directed therapies. These therapies are hypothesised to have disease-modifying effects by reducing the concentration of toxic forms of tau in the brain or by compensating for loss of tau function. Since tau pathology is also central to Alzheimer's disease and chronic traumatic encephalopathy, a successful tau therapeutic for PSP might inform treatment of other neurodegenerative diseases.